The Influence of Customer Satisfaction and Ease of Shopping on Payment Gateways in The Aqubeliaja Marketplace - Mu'min, Halek; Dharmayanti, Diah; Al Rizky, Farid (Westscience Press, 2024)
This study tests and proves whether customer satisfaction and ease of shopping have an influence on payment gateways in the aqubeliaja marketplace. The method used in the research is quantitative with an explanatory research approach. The data collection techniques used are questionnaires and documentation. The data analysis technique uses multiple regression with the help of SPSS software. The results of the multiple regression test show that the customer satisfaction variable b_1 = 0.276: is the regression coefficient value of the customer satisfaction variable X_1provides a value of 0.276 (positive sign) which means that if customer satisfaction increases by 1 unit, the payment gateway variable will increase by 0.200, while the value of b_2 = 0. 439 is the regression coefficient value of the ease of shopping variable X_2 provides a value of 0.439 (positive sign) which means that if the ease of shopping increases by 1 unit, the payment gateway variable will increase by 0.489, so it can be concluded that customer satisfaction and ease of shopping have a simultaneous effect. Customer satisfaction has an effect on payment gateways in shopping at aqubeliaja, this is evident in the SPSS test results which show that t_hitung14.430 and t_tabel1.65501 there is a linear relationship between customer satisfaction and payment gateway with a significant linearity of 0.000 <0.05. Ease of shopping has an influence on Payment gateway, the SPSS test results show that t_hitung11.638 and t_table1.65964 there is a linear relationship between customer satisfaction and payment gateway with a significant linearity of 0.000 <0.05. So it can be concluded that the payment gateway affects the ease of shopping at Aqubeliaja.